La fuerza constructiva y redentora de la rememoración en Walter Benjamin: a propósito de las memorias sobre la violencia en Colombia (2021)
This article explains the concept of remembrance (Eingedenkenken) in the light of Theses on the Philosophy of History (Über den Begriff der Geschichte, 1940), which from the Benjaminian Jewish perspective confers a redemptive quality to the suffering of the victims. Remembrance in Benjamin implies a messianic vision of politics and history, that is, a tool for the fight against the violence of oblivion and, at the same time, an ethical reference in the demand for reparation and justice. From a contextual reading of the theses, we think about the socio‑political implications and impacts of the exercise of memory in the Colombian reality, the contributions to the construction of a collective discourse on the truth of violence, and the challenges that the recognition of the voices of the victims imply in the construction of solid democracies and the establishment of guidelines for non-repetition.